Controlling release, unfolding and dissociation of membrane protein complexes in the gas phase through collisional cooling. Issue 85 (10th September 2015) - Landreh, Michael; Liko, Idlir; Uzdavinys, Povilas; Coincon, Mathieu; Hopper, Jonathan T. S.; Drew, David; Robinson, Carol V.
Abstract : Reduced collisional cooling releases intact membrane protein complexes from detergent micelles for unfolding and dissociation studies by mass spectrometry. Abstract : Mass spectrometry of intact membrane protein complexes requires removal of the detergent micelle by collisional activation. We demonstrate that the necessary energy can be obtained by adjusting the degree of collisional cooling in the ion source. This enables us to extend the energy regime for dissociation of membrane protein complexes.